Comparison of five early warning scores in predicting mortality risk in patients presenting to the emergency department with acute dyspnea: qSOFA, NEWS2, MEWS, HASI, and SIL - Ergün Süzer, Neslihan; Alpar, Süleyman; Tatlıparmak, Ali Cankut; Yılmaz, Sarper (The European Research Journal, 2025)
Objectives: This study aimed to compare five early warning scores - Quick Sequential Organ Failure Assessment (qSOFA), National Early Warning Score 2 (NEWS2), Modified Early Warning Score (MEWS), Hospital Alert Severity Index (HASI), and Shock Index-Lactate (SIL) - in predicting 30-day mortality in elderly patients presenting to the emergency department (ED) with acute dyspnea. Methods: This was a single-center, retrospective observational study. A total of 764 patients aged 65 years or older presenting to the emergency department with acute dyspnea over a five-year period were included in this study. The predictive accuracy of each score was evaluated using AUROC analysis and logistic regression. Results: Our findings demonstrated that the qSOFA score had the highest accuracy in predicting 30-day mortality (AUROC: 0.768). Among these scores, qSOFA showed the best performance in predicting mortality with a sensitivity of 72.9% and specificity of 74.6%. In logistic regression analysis, the qSOFA score demonstrated the strongest independent association with 30-day mortality (odds ratio [OR]: 5.23, P<0.001). The SIL score also showed a significant association with mortality (OR: 1.29, P=0.035). However, the HASI (P=0.092), MEWS (P=0.726), and NEWS2 (P=0.344) scores were not independently significant in multivariable analysis. Regarding mortality timing, qSOFA was identified as the most robust predictor for early death (within the first 3 days) with an AUROC of 0.801. It also demonstrated superior performance in predicting late in-hospital death (after 3 days) with an AUROC of 0.632 and post-discharge mortality within 30 days with an AUROC of 0.788. Other scores (HASI, MEWS, NEWS2, SIL) demonstrated lower performance in predicting mortality across different time intervals. Conclusions: qSOFA demonstrated the most consistent and accurate performance among the evaluated scores. It may serve as a practical tool for early risk stratification in elderly patients with acute dyspnea in ED settings.